Study of sharp injuries and blood splash exposures among healthcare workers in a tertiary hospital in Bangalore - Pradeep, Shalini Sivananjiah; Raghu, Suman Gadicherla; G, Prathab A; Rudresh, Banashankari G; Kunnavil, Radhika (International Journal of Infection Control, 2016)
The working environment of healthcare workers (HCW) exposes them to sharp injuries. This communication attempts to examine the injury registers, incidence of sharps injuries and blood splash exposures, and the post-exposure prophylaxis status of employees in a tertiary care hospital. Analysis included records form 54 locations of two units of a tertiary hospital attached to a Medical College. Maintenance of the injury register overall was highly satisfactory in both units. Two hundred and nine injuries were recorded from both units of the hospital. The majority of injuries (60.5%) occurred in the age group of 20-30 years with 70% among females. Waste handlers were at increased risk during waste management procedures. Thirty two percent of sharps injury injuries occurred in wards. Of the ward nursing staff, 25.3% received sharps injuries. Post-exposure prophylaxis for Hepatitis B (primary dose) was given to 25 HCWs; 11 received booster doses. The basic regimen for HIV post-exposure prophylaxis was given to 4 HCWs. Awareness about records maintenance, regular documentation, awareness and training, and implementation of appropriate preventive measures can reduce the incidence of injuries.Key words: Sharps, injury register, Health care workers (HCW),Post exposure prophylaxis (PEP)